2011
DOI: 10.4300/jgme-d-10-00173.1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Reliability of a Multisource Feedback Tool for Emergency Medicine Residents

Abstract: Background While the Accreditation Council for Graduate Medical Education recommends multisource feedback (MSF) of resident performance, there is no uniformly accepted MSF tool for emergency medicine (EM) trainees, and the process of obtaining MSF in EM residencies is untested. Objective To determine the feasibility of an MSF program and evaluate the intraclass and interclass correlation of a previously reported resident prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…3 In this study, we present a set of MSF instruments adapted for use in the ED setting from previously published instruments developed to measure resident behaviors across five core competencies in episodic care settings. While our pilot implementation of the instruments in eight diverse residency programs demonstrated excellent internal consistency (Cronbach's alpha = 0.96-0.97), we found that even with universal use of research assistants to facilitate data collection, it was difficult to achieve target numbers of assessments in all sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In this study, we present a set of MSF instruments adapted for use in the ED setting from previously published instruments developed to measure resident behaviors across five core competencies in episodic care settings. While our pilot implementation of the instruments in eight diverse residency programs demonstrated excellent internal consistency (Cronbach's alpha = 0.96-0.97), we found that even with universal use of research assistants to facilitate data collection, it was difficult to achieve target numbers of assessments in all sites.…”
Section: Discussionmentioning
confidence: 99%
“…2 Multisource feedback (MSF), or 360-degree feedback, is a workplace-based assessment method that has been piloted in a variety of U.S. specialties, including emergency medicine (EM), internal medicine, anesthesiology, pediatrics, and family medicine, and has been in use for assessment of practicing physicians by The College of Physicians and Surgeons of Alberta (CPSA) Physician Achievement Program for the past decade. [3][4][5][6][7][8] As part of the CPSA's work, a set of MSF instruments was created for physicians who provide episodic care (including emergency physicians, locum physicians, physicians serving walk-in populations, urgent care physicians, hospitalists, and niche or specialty primary care physicians such as family planning and low-risk obstetrics). These instruments included specific questionnaires for patients, physician colleagues, nonphysician colleagues, and self-assessment.…”
mentioning
confidence: 99%
“…A previously reported instrument assessing EM resident interpersonal skills, attitudes, and behaviors, the Emergency Medicine Humanism Scale (EM‐HS), was used to obtain feedback. The EM‐HS is a MSF instrument that can be reliably administered to patients, nonphysician staff, and supervising faculty physicians 6 . The EM‐HS consists of nine questions for health care providers (Figure 1) with ratings on a nine‐point continuum from “needs improvement” to “outstanding.” The EM‐HS has previously demonstrated excellent generalizability coefficients within nurse and faculty rater groups (Eρ 2 = 0.83 and 0.79, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…It was found to be a feasible, reliable, and valid tool. Garra et al 32 studied an MSF tool, the EM-Humanism Scale, which evaluated U.S. EM residents' professionalism and interpersonal and communication skills. The instrument had good reliability for nurses and faculty, but only fair reliability for patient ratings.…”
Section: Ratings-and Survey-based Assessment Toolsmentioning
confidence: 99%